Health Education at the Spanish school (1970-1990): Challenges at the intersection of fields of knowledge - Hurtado-García, Inma; Terrón-Bañuelos, Aida (Historia y Memoria de la Educación, 2021)
The context of interpellation of international guidelines, the discursive effervescence around health reform in the 1970s and the absence of health education in the curriculum created the ideal conditions for the debate on the future of Health Education in the school environment. From the respec¬tive sectoral actions—especially from the health field—as well as from their synergies, a theoretical body and a conglomerate of practices emerged which served to structure and consolidate the field. A reflection was undertaken on the notion of health and on the context of the school as a fundamental locus from which to build a new social framework of responsibility in health. Likewise, the aim was to cover what the curriculum did not yet offer, i.e. the organisation of experiences, campaigns and various programmes with which to encourage community participation.